INTERNAL POLITICAL AND ECONOMIC PROCESSES IN UKRAINE (PERIOD OF V. YANUKOVICH RULING) - K. G. Ilinova (Проблемы постсоветского пространства)
This paper investigates the period of Victor Yanukovich ruling. His economic policy allowed for keeping the situation under control, not admitting deterioration of the social conditions of the people. The internal and foreign policy was fraught with controversies which, finally, had led to a political crisis.